Agro-Entrepreneurial Intention: Testing the integrated Model of Psychological and Behavioral (TPB) Approaches - Ezeh, Precious Chikezie; Abdulrahman, Rufai Mohammed (Acta Universitatis Danubius. Œconomica, 2022)
This study explored the influence of behavioural and psychological traits on agro-entrepreneurial intentions among secondary school students. Secondary school students aged 15-19 years were selected. Data were collected using 300 pieces of questionnaire, and structural equation modelling (SEM) was used for analysis. It was found that secondary school students' agro-entrepreneurial intention is significantly and positively related to perceived behavioural control, attitude towards behaviour and tolerance for ambiguity but significantly and negatively related to self-confidence. This study offers evidence of the effects of behavioural and psychological traits of secondary school students on agro-entrepreneurial intentions. This study explicitly focused on secondary school students. The findings provide valuable information for curriculum and policy development.